PHYSICS E-MODULE WITH A SCIENTIFIC APPROACH ON GLOBAL WARMING MATERIAL FOR GRADE 10: E-MODULE FISIKA DENGAN PENDEKATAN SAINTIFIK PADA MATERI PEMANASAN GLOBAL UNTUK KELAS 10 - Syafira Ghassani; Vina Serevina; Esmar Budi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This research is to design learning media that can be used anytime and anywhere, to follow student learning culture in current technological developments. The research uses research and development (R&D) methods, with a 4D research model (Define, Design, Develop, and Disseminate). Initial research data collection at the Define stage was carried out by observing at school, interviews with teachers and students, and giving questionnaires to students. Based on data analysis, students need learning media that is practical, can be used anywhere and at any time, and they agree to carry out research by designing e-modules with a scientific approach to global warming material. The expected results of this e-module are that students are more interested in learning, have easier access to learning resources, and can be used for students with diverse learning characteristics, because it is equipped with various pictures, explanatory videos and questions related to global warming in the e-module . Data collection in this research was carried out by giving questionnaires to media experts and learning experts, as well as questionnaires to physics teachers and students.